2014
DOI: 10.7314/apjcp.2014.15.12.4885
|View full text |Cite
|
Sign up to set email alerts
|

Does Clinical Experience Help Oncology Nursing Staff to Deal with Patient Pain Better than Nurses from other Displines? Knowledge and Attitudes Survey Amongst Nurses in a Tertiary Care in Malaysia

Abstract: Background: Successful implementation of pain management procedures and guidelines in an institution depends very much on the acceptance of many levels of healthcare providers. Aim: The main purpose of this study was to determine the level of knowledge and attitudes regarding pain among nurses working in tertiary care in a local setting and the factors that may be associated with this. Materials and Methods: This cross-sectional research study used a modified version of the Nurses' Knowledge and Attitudes Surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 32 publications
0
9
1
Order By: Relevance
“…Bakey et al showed that there was no significant relationship between nurses' practice and their age, whereas there was a significant relationship between nurses' practice and their age in another study [5]. A different study also demonstrated that neither years of nursing experience nor age influenced the behaviors of nursing staff [17]. In our study, the total score of answers was 29.2 (±10.4) out of 70.…”
Section: Discussioncontrasting
confidence: 57%
“…Bakey et al showed that there was no significant relationship between nurses' practice and their age, whereas there was a significant relationship between nurses' practice and their age in another study [5]. A different study also demonstrated that neither years of nursing experience nor age influenced the behaviors of nursing staff [17]. In our study, the total score of answers was 29.2 (±10.4) out of 70.…”
Section: Discussioncontrasting
confidence: 57%
“…It is important to find instruments that are reliable and valid, but also have suitable content for assessing nurses' expertise in palliative care nursing. Several instruments have been used to evaluate nurses’ competence in palliative care (Hujer et al, ; Bing‐Jonsson et al, ; Mager & Lang, ; Yaakup et al, ), and competence assessment is assumed to significantly improve the skills of nurses (Desbiens et al, ). In this integrative review, the content of the ten instruments for measuring nurses’ palliative care knowledge and skills can be separated into three different categories: (a) care for the patient, (b) care for the patient's family and (c) professional requirements (Table ).…”
Section: Discussionmentioning
confidence: 99%
“…The self‐assessment of competence has been shown to develop the palliative care skills of nurses and improve the quality of care (Desbiens, Gagnon, & Fillion, ). A range of measurement indicators has been used to assess nurses’ competence in palliative care (Huijer et al, ; Bing‐Jonsson, Bjork, Hofoss, Kirkevold, & Foss, ; Mager & Lang, ; Yaakup, Eng, & Shah, ); however, there is no consensus on the instruments for measuring nurses’ palliative competence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Darunee Jongudomkarn 1 *, Colin Macduff 2 and organizations (Kostak et al, 2014;Sercekus et al, 2014;Taylor et al, 2013;Yaakup et al, 2014). Accordingly it is important to learn from initiatives taken forward in this field.…”
Section: Development Of a Family Nursing Model For Prevention Of Cancmentioning
confidence: 99%